Kriminalisasi Kohabitasi: Tantangan Penegakan Hukum dalam Keberagaman Budaya Indonesia - Komang Yudiani; Made Sugi Hartono; I Nengah Suastika (Perspektif Administrasi Publik dan hukum, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code introduces the criminalization of cohabitation under Article 412, sparking public debate regarding state intervention in private spheres. This research aims to analyze the challenges faced by law enforcement in implementing cohabitation regulations within Indonesia’s pluralistic society. Utilizing a normative judicial research method with statute and conceptual approaches, this study examines secondary legal data including the New Criminal Code and various legal doctrines. The findings indicate that while Article 412 is designed as an absolute complaint-based offense to balance institutional marriage protection with individual privacy, its implementation faces substantial sociological hurdles. These challenges include potential conflicts with living law such as customary and religious norms, risks of over-criminalization, and the threat of social vigilantism due to public misinterpretation. This research implies that law enforcement must prioritize restorative justice and intensive socialization to prevent human rights violations and maintain social harmony in a diverse cultural landscape.